Holmium-166 Radioembolization of Hepatic Metastases in Salvage Setting: Preliminary Findings from a Single Center Experience - Dökdök, Murat; Berberoğlu, Kezban (Journal of Clinical Interventional Radiology ISVIR, 2023)
Purpose The aim of this study is to report the early outcomes of holmium-166 (166Ho) radioembolization in the treatment of liver metastases.Methods Nine patients with liver metastases originating from different primary sites were treated with 166Ho radioembolization between January 2019 and February 2020. The patients were assessed for pain using a visual analog scale (VAS) and quality of life (QoL) at various intervals during hospitalization and follow-up. Toxicity that may be attributable to radioembolization was graded according to CTCAE v5.0. The tumor dosimetry and tumor response were assessed with anatomic and metabolic imaging.Results The mean tumor dose was 150 Gy, 95% confidence interval (CI) was 135.2 to 164.8, with a range of 100 to 200 Gy based on single-photon emission computed tomography (SPECT)/CT, and distribution verified with inline T2/R2* magnetic resonance imaging (MRI) maps. No early (30-day) mortality or grade greater than 2 toxicities were noted, but one patient had chylous ascites. QoL assessed with the European Quality of Life 5-Dimensions 3-Level version (EQ-5D-3L) revealed mean index scores of 0.748 (range: 0.5–1), 95% CI of 0.6 to 0.9, before the procedure, and 0.7 (range: 0.5–1) and 95% CI of 0.6 to 0.8, at 1 month. The mean VAS was 70.6, 95% CI was 65.5 to 75.6, immediately after the procedure, and decreased to the mean VAS of 65.7 and 95% CI of 55.9 to 75.5 after 1 month. Five patients showed a partial response, three showed a stable disease, and one showed progressive disease at the first 2- to 3-month imaging follow-up.Conclusion Radioembolization with 166Ho microspheres for liver metastases appears to be safe, tolerable, and effective during the short term in this small-scale study.
Keywords: holmium-166 microspheres; radioembolization; liver metastases